Grid computing for bioinformatics and computational biology - Talbi, El-Ghazali, 1965-; Zomaya, Albert Y. (Hoboken, N.J. : Wiley-Interscience, 2008)
Provides details on modern and ongoing research on Grid applications. This book discusses bio ontology and data mining; data visualization; DNA assembly, clustering, and mapping; molecular evolution and phylogeny; gene expression and micro arrays; gene identification and annotation; and molecular modeling and simulation.
GRID COMPUTING FOR BIOINFORMATICS AND COMPUTATIONAL BIOLOGY; CONTENTS; Preface; Acknowledgments; Contributors; 1. Open Computing Grid for Molecular Sciences; 2. Designing High-Performance Concurrent Strategies for Biological Sequence Alignment Problems on Networked Computing Platforms; 3. Optimized Cluster-Enabled HMMER Searches; 4. Expanding the Reach of Grid Computing: Combining Globus- and BOINC-Based Systems; 5. Hierarchical Grid Computing for High-Performance Bioinformatics; 6. Multiple Sequence Alignment and Phylogenetic Inference.
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Bioinformatics; Computational biology; Computational grids (Computer systems); Computational Biology; Bio-informatique.; Grilles informatiques; NATURE -- Reference; SCIENCE -- Life Sciences -- General; SCIENCE -- Life Sciences -- Biology; Bioinformatics; Computational biology; Computational grids (Computer systems)